How do Indonesian students respond to ethnomathematics-based learning in the digital era? - Payadnya, I Putu Ade Andre; Wibawa, Kadek Adi; Jayantika, I Gusti Agung Ngurah Trisna; Wena, I Made; Puspadewi, Kadek Rahayu (Indonesian Journal of Science and Mathematics Education, 2024)
The integration of ethnomathematics ((a combination of mathematical concepts with local culture) into education presents unique opportunities and challenges, particularly in the digital era where cultural and technological contexts converge. This study explores the responses of eighth-grade students in Indonesia to ethnomathematics-based learning centred on Balinese culture. Employing a qualitative descriptive approach, 42 students participated in interviews and essay tests designed to assess their abilities in solving culturally embedded mathematical problems. The findings reveal a strong enthusiasm among students, who found the approach engaging and novel. However, significant difficulties emerged in connecting mathematical concepts to cultural contexts, exposing a gap between student interest and problem-solving capabilities. The implications of this study underscore the urgent need for culturally responsive teaching methodologies capable of bridging the gap between theory and practice in the digital educational landscape. These findings provide a new direction for innovations in ethnomathematics education relevant to the needs of the 21st century.